Novel Foods and Edible Insects in the European Union An Interdisciplinary Analysis - Scaffardi, Lucia; Formici, Giulia (Springer International Publishing : Imprint: Springer, 2022)
This open access book proposes an in-depth study on a vast range of issues connected to the regulation of Novel Foods in the European Union, pursuing an interdisciplinary approach and thus providing a comprehensive picture of this complex topic. Particular attention is paid not only to the current EU legislative framework, its positive innovations, unsolved problems and limits, but also to food safety issues and the potential impact of Novel Foods on sustainability and food security. In addition, the book focuses on a particular category of Novel Foods: insects for human consumption. These products recently gained momentum after the first EU Commission authorisation of dried yellow mealworm (Tenebrio molitor) in 2021. The book contributes to the lively public debate following this long-awaited authorisation by examining the legal issues arising from the application of the Novel Foods Regulation to these peculiar new foods; the EFSA risk assessment evaluations; the consumers' perceptions and potential future of insect-based products' market in the EU. By providing such an extensive analysis, including recent developments and future prospects, the book represents a valuable tool for students and academics, but also institutions and public authorities, helping them understanding the various challenges related to Novel Foods and edible insects. Furthermore, it seeks to promote an informed debate in order to find innovative solutions to pressing problems concerning how to feed the world of tomorrow.